Resumo à luz da teoria da argumentação na língua - Camacho, Pâmela Nataline de Oliveira (2015)
This paper proposes the elaboration of summaris, based o the Argumentation Theory within the Language. The objective is to identify, in a text-base, through a reflective reading, what are the meanings presented by the author that are essentials and which are acessories, establishing a favorable condition for the preparation of the summary. The Argumentation Theory within Language, in particular, in its a theoretical proposal that explains how the meanings is constructed by the relationship among signs and how these signs are related to others, guiding for possible and impossible combinations in the view of the speech. It is believed that it is possible to identify the essentials meanings and the accessories contained in the text, since the meaning consists of argumentative chains, in other words, chains of the meaning. Those meanings that are not continued should not be included in the summary, because they are considered accessories. We further assume that through argumentative links, which are build, it is possible, in a concrete way, to observe how the different meanings presented in a text are related.